Implementasi Islamic Corporate Governance Dalam Mengelevasi Corporate Social Responsbility - Saiful Muchlis; Resky Resky (Universitas Muhammadiyah Jakarta, 2021)
This study aims to determine the Corporate Social Responsibility (CSR) programs with their suitability to Islamic Corporate Governance (ICG) carried out by BNI Syariah KCU Makassar. This study used a descriptive qualitative research method. Data collection used in depth interview to informants and information from internet as a complement. The results of this study are, first, the CSR program implemented by BNI Syariah KCU Makassar always follows the Central BNI Syariah Program. Second, CSR program of BNI Syariah KCU Makassar is accordance with ICG based on the mandate value and the concept of maqashid sharia. Third, the implementation of ICG values in CSR program of BNI Syariah KCU Makassar is able to evaluate CSR and has met the principles of transparency and accountability